Synthesis and biological evaluation of 3, 5-disubstituted-4-alkynylisoxozales as a novel class of HSP90 inhibitors. Issue 16 (15th August 2015) - Sun, Jian; Lin, Cai; Qin, Xiaochu; Dong, Xiaoping; Tu, Zhengchao; Tang, Fei; Chen, Chaonan; Zhang, Jiancun
Graphical abstract: Abstract: A series of 3, 5-disubstitute-4-alkynylisoxazole derivatives were designed and synthesized through palladium(II)–copper(I) catalyzed Sonogashira cross-coupling reaction of an alkynyl moiety and an isoxazole scaffold as novel HSP90 inhibitors. The resultant compounds displayed moderate to potent binding affinity to HSP90 proteins, and also demonstrated good cell growth inhibitory activity against various cancer cell lines (A549, K562, MCF-7, DU145 and Hela). Some compounds (18d, 18e, 19a, 19d, 20c and20q ) show similar or better binding affinity towards HSP90α and HSP90β comparing to NVP-AUY922. In addition, compounds18e, 19a and20q exhibited potent inhibitory activity against various human cancer cell lines.